The granulate ambrosia beetle, Xylosandrus crassiusculus (Coleoptera: Curculionidae, Scolytinae), and its fungal symbiont found in South Africa - Nel, Wilma J.; de Beer, Z. Wilhelm; Wingfield, Michael J.; Duong, Tuan A. (Zootaxa, 2020)
Xylosandrus crassiusculus (Motchulsky) is a native Asian ambrosia beetle that has been accidentally introduced to many countries of the world, presumably through the international movement of nursery, timber, and wood products. The species is known in various tropical African countries but only as far south as Tanzania on the African continent. In this study, we report X. crassiusculus and its fungal symbiont for the first time from South Africa. The species was identified using both morphological characters and COI sequence data. Xylosandrus crassiusculus were obtained from three different provinces of South Africa and represent two distinct haplotypes. The fungal symbiont, Ambrosiella roeperi, was isolated and identified using DNA sequencing and morphological characterization.